Quantum Computing: Algorithms,Architectures, and Applications - Alghamdi Wajdi; Salama Reda; S Hemalatha; Alzubaidi Laith H.; Akrom Uzakov; Senthilkumar R (E3S Web of Conferences, 2023)
Cryptography, optimization, simulation, and machine learning are just a few of the industries that might be completely transformed by quantum computing. This abstract gives a thorough introduction to quantum computing with an emphasis on its algorithms, architectures, and applications. In conclusion, this abstract offers an in-depth analysis of quantum computing, including its algorithms, structures, and applications. It highlights the revolutionary potential of quantum computing in tackling difficult issues that are beyond the scope of conventional computers, laying the groundwork for further research and understanding of this quickly developing topic.